The Influence of Financial Literacy, Experienced Regret, Framing Effect and Mental Accounting on Millennial Generation Investment Decisions in DKI Jakarta with Risk Tolerance as Intervening Variables - Monica Dewi; Hamidah Hamidah; Agung Dharmawan Buchdadi (International Journal on Advanced Science, Education, and Religion, 2021)
This study discusses financial literacys, experienced regrets, framing effect and mental accounting on investment decisions with risk tolerance as an intervening variable. The number of respondents used in this study was 200 respondents. All respondents are millennials with age 21-40 years old and have a minimum income of IDR 5,000,000, who live in DKI Jakarta. The data in this study were obtained from the results of questionnaires which were then analyzed using SEM PLS analysis techniques with the help of the smartpls program. Based on the results of the analysis in this study the results of financial literacy, experienced regret, framing effects and mental accounting are applied to risk tolerance. The results of the subsequent analysis showed that financial literacy, regrets and framed the effect of influencing on investment decisions, while mental accounting directly cannot influence on investment decisions. The results of the analysis in this study also showed that risk tolerance can mediate the financial literature, experience regret, and the effect of framing on investment returns. Keywords: Financial Literacy, Experienced Regrets, Rraming Efects, Milenial Generation Investment